Calculation of Control Rods Reactivity Worth of RSG-GAS First Core Using Deterministic and Monte Carlo Methods - T. Surbakti; S. Pinem; T.M. Sembiring; A. Hamzah; K. Nabeshima (PPIKSN-BATAN, 2019)
The control rod worth is a key parameter for the research reactor operation and utilization. Control rod worth computation is a challenge for the fully-deterministic and Monte Carlo calculations, including the few-group cross section generation, and the core analysis. The safe and reliable utilization of research reactor demands the possible accurate information of control rod worth because they are used to compensate the excess reactivity for safe reactor operation and its controlled shut down. The criticality positions of the control rods change with time due to buildup of fission products during the reactor operation. It is therefore important to determine the reactivity worth of control rods. The aim of this article is to obtain reliable control rod worth of the first core of RSG-GAS as a verification and validation result. For this purpose, deterministic and Monte Carlo models of the reactor core were developed and confirmed by the experimental results of excess reactivity, shutdown margin, and combined control rod reactivity worth using the combination of WIMSD-5B and Batan-3DIFF computer codes. WIMSD-5B is a neutron transport theory-based lattice cell modeling code that is used for the generation of group constants for different regions of the reactor core. These are provided as input to the diffusion theory based Batan-3DIFF code which performs the global core calculations for the reactor system. For the Monte Carlo model, to estimate the reactivity worth of control rods, the MCNP6 code is used. The result of this analysis showed that for the integral control rod worth a good agreement was found between experimental data and Monte Carlo simulation results but up to 5 % difference occurred between experimental results and diffusion result.